A dual-channel optical magnetometer based on magnetically responsive inverse opal microspheres. Issue 36 (28th June 2017) - Zhang, Yuqi; Jiang, Yitong; Wu, Xiaojie; Ge, Jianping
Abstract : The chain assembly of inverse opal microspheres in a ferrofluid and their reflection quenching are used to detect magnetic field strength. Abstract : Responsive photonic crystals (RPCs) with tunable optical signals have intrinsic advantages in the construction of colorimetric sensors. Here, we report a dual-channel photonic crystal sensor fabricated by suspending ETPTA-TPM inverse opal microspheres (IOMs) in an aqueous ferrofluid for the detection of magnetic field strength. These nonmagnetic IOMs will quickly arrange into chain structures along the field direction, leading to the quenching of reflection signals in several minutes. Generally, a stronger magnetic field causes a faster quenching and a larger decline of reflection intensity. Based on the above correlation, a dual-channel sensor was fabricated to detect magnetic field strength in a broad range according to reflection quenching time and quenching ratio. The sensing of the magnetic field is accurate, stable and reliable, because the working of the PC sensor only involves magnetic tuning but no magnetic assembly.